The role of serum nesfatin-1 in predicting metabolic syndrome among patients with overweight - Alsarraf, Z.; Mohammed, M. H.; Haitham, F. (Regulatory Mechanisms in Biosystems, 2025)
Nesfatin-1 biomarker could have a promoting key role in the diagnosis and management of many metabolic disorders. However; till now, the exact role of nesfatin -1 in human s still need s further studies. The study presented here was conducted on 40 individuals who were divided into two groups, 20 patients with metabolic syndrome (cases) and 20 healthy people (controls). In addition to sociodemographic and anthropometric measurements, circulating levels of serum lipid profile, fasting blood sugar, insulin resistant (HOMA), serum nesfatin -1 level were measured. All of the study participants also had their blood pressure measured. No significant difference was found between the two groups regarding nesfatin -1 level, but nesfatin -1 was significantly in negative correlation with serum triglyceride , and lastly nesfatin -1 showed accepted prediction outcome of metabolic syndrome.